Identifying and Analyzing the Dimensions and Components of Strategic Decision-Making for the Managers of Education Regions of Tehran City - Nikpour Sardahai, Fereshteh; Doshman Ziari, Esfandiar; Kiumarsi, Firouz; Esmailzadeh, Zohreh; Sharifian, Leila (Iranian Journal of Educational Sociology, 2022)
Purpose: Strategic decision-making plays an important role in organizational functions and its effectiveness. As a result, the aim of this study was to identifying and analyzing the dimensions and components of strategic decision-making for the managers of education regions.Methodology: This study in terms of purpose was applied and in terms of implementation method was mixed (qualitative and quantitative). The research population were experts in the field of educational management and human resources management and managers of educational regions of Tehran city in 2021 year, which according to the principle of theoretical saturation number of 14 people of them were selected as a sample with using the purposeful sampling method. The research tool was a semi-structured interview that lasted 75 to 120 minutes, and their validity was confirmed by the triangulation method and their reliability was obtained by the agreement coefficient method between two coders 0.88. The data were analyzed by methods of thematic analysis and DIMTEL technique.Findings: The findings of the qualitative part showed that strategic decision-making for managers of education regions has 98 indicators, 23 components and 10 dimensions were include moral intelligence, individual skills, knowledge of organizational processes, cultural and value skills, knowledge of financial resources, power of change and transformation, knowledge and technology management, human resource management, intelligent planning and training. Also, the findings of the quantitative part showed that the dimensions of human resource management, intelligent planning, cultural and value skills, knowledge of financial resources, knowledge and technology management and training had more effective and the dimensions of knowledge of organizational processes, moral intelligence, individual skills and power of change and transformation had more influence.Conclusion: The findings of this study have practical implications for specialists and planners of educational systems, especially in the education system, and they based on the results of the present study, can take an effective step towards strategic decision-making.